2015
DOI: 10.1063/1.4922147
|View full text |Cite
|
Sign up to set email alerts
|

Hardness, elastic, and electronic properties of chromium monoboride

Abstract: Articles you may be interested inElastic anisotropy and shear-induced atomistic deformation of tetragonal silicon carbon nitride Hardness and incipient plasticity in silicate glasses: Origin of the mixed modifier effect Appl. Phys. Lett. 104, 051913 (2014); 10.1063/1.4864400 Experimental verification and theoretical analysis of the relationships between hardness, elastic modulus, and the work of indentation Appl. Phys. Lett. 92, 231906 (2008); 10.1063/1.2944138Ground-state properties and hardness of high densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 24 publications
1
35
1
1
Order By: Relevance
“…The plateau is an indication of transition from elastic to plastic deformation, and so these data indicate that the (020) planes constitute the primary slip system for this material, in agreement with calculations on isostructural CrB. [17] While these factors all suggest that the metal bilayers are the weakest directions in the material, the actual plateau value of 5.1% dif ferential strain is quite high. We note that unlike differential stress, differential strain cannot be directly related to hardness because elastic anistropy can produce high strains in elasti cally soft directions.…”
Section: Communicationsupporting
confidence: 61%
See 1 more Smart Citation
“…The plateau is an indication of transition from elastic to plastic deformation, and so these data indicate that the (020) planes constitute the primary slip system for this material, in agreement with calculations on isostructural CrB. [17] While these factors all suggest that the metal bilayers are the weakest directions in the material, the actual plateau value of 5.1% dif ferential strain is quite high. We note that unlike differential stress, differential strain cannot be directly related to hardness because elastic anistropy can produce high strains in elasti cally soft directions.…”
Section: Communicationsupporting
confidence: 61%
“…Indeed, computational studies of isostructural chro mium monoboride have shown that the metal bilayer is indeed a slip plane. [17] As a result, if we can prevent dislocations in this metallic plane, we should be able to increase the overall hard ness of tungsten monoboride.…”
Section: Doi: 101002/adma201601187mentioning
confidence: 99%
“…These easy-glide planes govern the formation and movement of dislocations and thus dominate the intrinsic hardness. Indeed, the high-pressure radial diffraction experiment of W 0.5 Ta 0.5 B 34 and the calculated study of CrB 38 have corroborated the presence of the weak slip planes. Similar behaviors also occur in other structural systems.…”
Section: Resultsmentioning
confidence: 66%
“…Transitionmetal borides with anisotropic bonding within the crystal structure and high volume expansion upon oxidation are promising interphase materials for future UHTC f /UHTC composites. Although the structural, elastic properties of transition-metal monoborides have been studied by several groups, [15][16][17][18] investigation on the electronic structure, chemical bonding, and elastic properties of NiB is scarce. NiB was selected due to the following reasons.…”
Section: Introductionmentioning
confidence: 99%
“…(1) The crystal structure and bonding properties of borides are diverse so that their properties are tunable; 14 (2) As we will see in later sections, NiB has high bulk modulus but low shear resistance, which can allow crack deflection from matrix in UHTC f /UHTC composites; and (3) Upon high-temperature oxidation, the volume will expand by forming B 2 O 3 and NiO to protect the UHTC fibers. Although the structural, elastic properties of transition-metal monoborides have been studied by several groups, [15][16][17][18] investigation on the electronic structure, chemical bonding, and elastic properties of NiB is scarce. Understanding how elastic properties are related to the fundamental electronic structure is a subject of great importance if application of NiB as an interphase material for future UHTC f /UHTC composites is envisioned.…”
Section: Introductionmentioning
confidence: 99%